Computed Tomography Study of the Mummy of King Seqenenre Taa II: New Insights Into His Violent Death - Saleem, Sahar N.; Hawass, Zahi (Frontiers in Medicine, 2021)
Seqenenre-Taa-II, The Brave, (c.1558- 1553 BC) ruled Southern Egypt during the occupation of Egypt by the Hyksos. The mummy was physically examined and X-rayed in the 1960s, which showed severe head wounds that have prompted various theories about the circumstances of his death. We postulated that Computed Tomography (CT) study of Seqenenre-Taa-II’s mummy would give insights into the circumstances of his death. We examined Seqenenre’s mummy using CT and compared the findings with the archaeological literature as well as with five Asian weapons found in Tell-el-Dabaa. CT findings indicate that Seqenenre died in his forties. The mummies deformed hands suggest that the King was likely imprisoned with his hands tied. CT images provided detailed analysis of Seqenenre’s previously reported injuries to the forehead, right supra-orbital, nose-right orbit, left chick, and skull base. This study revealed additional craniofacial fractures in the right lateral side of the skull that had been concealed by the embalmers beneath layers of material. Analysis of the morphology of the injuries enabled a better understanding of the mechanism of trauma, possible number of the attackers, and their relative position to the King. The size and shape of the fractures correlated well with the studied Hyksos weapons. The lethal attack was aimed at the King’s face, likely in an attempt to disgrace him. Mummification of Seqenenre’s body was limited to evisceration without brain removal. The desiccated brain is shifted to the left side of the skull. This may indicate that the King’s dead body stayed on its left side for some time -- long enough for decomposition start before the mummification began. This suggests that the King likely died at a location distant from the funeral place, possibly on a battlefield. The embalmers attempted to conceal the King’s injuries; the methods used suggest that the mummification took place in a royal mummification workshop rather than in a poorly equipped location. CT findings of Seqenenre’s mummy helped us to better understand the circumstances of his violent death. His death motivated his successors to continue the fight to unify Egypt and start The New Kingdom.